Nuxt.js : Vue.js on steroids (Packt Publishing, 2018)
"This course will take you on a journey where you'll you will learn to build highly engaging Vue.js apps with Nuxt.js. Nuxt adds easy server-side-rendering and a folder-based config approach. Vue.js is an amazing JavaScript framework which you can use to build highly engaging user interfaces and single.- page applications. You'll master all the details in this course but the most important takeaway is that Nuxt.js makes creating better, more optimized, and more capable Vue apps much easier--and all of that while adding pretty much no overhead. You'll learn how to create Nuxt/ Vue apps from scratch! You'll build an entire course project and dive into the core features Nuxt.js offers. By the end of the course, you'll have a complete Vue app, built with Nuxt.js, which can be rendered on the server (or as a static website!) and which is highly optimized."--Resource description page